2016
DOI: 10.19044/esj.2016.v12n21p186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of African Giant Snails For Parasites In A South-East Region Of Côte d'Ivoire

Abstract: Two species of snails (Achatina achatina and Archachatina ventricosa), from surrounding forest of Azaguié’s district, were collected at the market of the locality aforementioned in order to identify their various parasites. For that, 50 snails of each species were sacrificed. Parasites were searched on the level of the flesh, between the flesh and the shell, the stomach, the intestine, the liver and the reproductive apparatus. The collected parasites were Balantidium spp, the larvae of Protostrongylus spp, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…Snails are found mostly on dirt or soil scavenging for food or reproducing, and because of this, parasites may infect snails. The prevalence in this study is high when compared with the works ofOkwa et al (2022) & Karamoko et al (2016 who reported 33.…”
contrasting
confidence: 64%
“…Snails are found mostly on dirt or soil scavenging for food or reproducing, and because of this, parasites may infect snails. The prevalence in this study is high when compared with the works ofOkwa et al (2022) & Karamoko et al (2016 who reported 33.…”
contrasting
confidence: 64%
“…Cependant, il faut souligner la complexité de la relation hôte -parasite qui définit la parasitologie moderne. En effet, les parasites sont plus ou moins adaptés à une ou plusieurs espèces d'hôtes (Karamoko et al, 2016), leur permettant un développement complet. Il arrive parfois que le cycle évolutif des parasites soit interrompu lorsqu' il n'y a aucune spécificité parasitaire avec son hôte.…”
Section: Introductionunclassified